Key Development Challenges Around Internal Displacement : A Gender Perspective - Klugman, Jeni (World Bank, Washington, DC, 2022)
At the end of 2020, there were over 48 million internally displaced persons (IDPs) displaced by conflict and another seven million displaced by natural disasters, more than double the number of refugees. The challenges facing IDPs are often less visible than those facing refugees, although accumulating evidence does point to systematic disadvantages, especially for women and girls. This paper charts the extent to which national and international policies and programs address gender in displacement settings. Our review finds that while there has been important progress, major shortcomings persist in addressing the gendered dimensions of internal displacement at the international and country levels. Commitments on paper have not consistently translated to change in practice. Gender gaps in livelihoods, social protection, durable solutions, gender-based violence, health, and education as major challenges requiring increased attention.